Teacher Education in the Nordic Region Challenges and Opportunities - Elstad, Eyvind (Evaluating Education: Normative Systems and Institutional Practices, 2023)
This open access book is the first account of the whole diversity of teacher education in the Nordic region: Norway, Sweden, Finland, Denmark, Iceland, Greenland, the Faroe Islands, the Åland Islands and Sápmi (where the Sámi people live). Today, large parts of the world are looking to the Nordic model of social organization, and interest in the Nordic comprehensive school system and teacher education arrangements is no exception. A good education is a key to prosperity and well-being. And the quality of students' education is undoubtedly linked to the quality of their teachers' education. While teacher education in the Nordic region is globally admired, it also faces new challenges. The leading scholars writing in this volume discuss the challenges and opportunities that professional environments are facing. By providing solid portraits of each area as well as analyses across the region, this book will be a great resource to students, academics in teacher education and schooling as well as social scientists and policy-makers inside and outside the Nordic region. This is an open access book.